Stable and durable CH3NH3PbI3 perovskite solar cells at ambient conditions. (29th April 2016) - Rajamanickam, Nagalingam; Kumari, Sudesh; Vendra, Venkat Kalyan; Lavery, Brandon W; Spurgeon, Joshua; Druffel, Thad; Sunkara, Mahendra K
Abstract: Degradation of metal−organic halide perovskites when exposed to ambient conditions is a crucial issue that needs to be addressed for commercial viability of perovskite solar cells (PSCs). Here, a concept of encapsulating CH3 NH3 PbI3 perovskite crystals with a multi-functional graphene–polyaniline (PANI) composite coating to protect the perovskite against degradation from moisture, oxygen and UV light is presented. Hole-conducting polymers containing 2D layered sheet materials are presented here as multi-functional materials with oxygen and moisture impermeability. Specific studies involving PANI and graphene composites as coatings for perovskite crystals exhibited resistance to moisture and oxygen under continued exposure to UV and visible light. Most importantly, no perovskite degradation was observed even after 96 h of exposure of the PSCs to extremely high humidity (99% relative humidity). Our observations and results on perovskite protection with graphene/conducting polymer composites open up opportunities for glove-box-free and atmospheric processing of PSCs.